Gene therapy strategies for aging intervention - Yaobin Jing; Jie Ren; Jing Qu; Guang-Hui Liu (Cell Insight, 2025)
Aging is characterized by a progressive decline in organ and tissue structure and function, significantly increasing the risk of many chronic diseases. Developing interventions to delay aging holds the potential to reduce the burden of age-associated diseases and promote healthy longevity. Gene therapy has emerged as a clinically transformable approach, leveraging advanced gene editing and delivery systems to target the molecular underpinnings of aging. This review systematically explores the potential of gene therapy strategies in aging intervention, focusing on approaches that enhance genomic and epigenetic stability, restore metabolic homeostasis, modulate immune responses, and rejuvenate senescent cells. By providing a comprehensive overview and forward-looking insights, this article aims to inform future research directions and translational applications of gene therapy in mitigating aging-related decline.